Experiencias adversas en la infancia y secuelas en las relaciones interpersonales - Robayo Quevedo, Wendy Madelaine; Aguilera Pinzón, María Cristina (My University, 2024)
Adverse childhood experiences (AIE) are negligent acts that occurred in the individual's childhood, which can be traumatic and affect the well-being of the subject. On the other hand, interpersonal relationships are the ties created by the person with other individuals, which can be affected if they suffer some type of violence. The objective of this study is to determine the impact of adverse experiences on the interpersonal relationships of young adults. A study was carried out with a descriptive scope and a qualitative approach. For this research, a sample of 4 young adult participants was used, two male from Machala and two female from Pasaje, where their ages ranged from 20 to 25 years, who suffered from some adverse event in their childhood. The instruments used are the semistructured interview, which allowed valuable information to be collected about the adverse experiences suffered by the participants, and in turn to know how these influence interpersonal relationships; The adverse experiences questionnaire was also applied to them, which allowed them to evaluate the negative experiences they have suffered in their childhood. Obtaining as a result that EAI does influence interpersonal relationships, since it manifested itself in the difficulty in trusting others, conflict resolution, quality of establishing new relationships, personal description, daily activities effectively and current emotions. Finally, it is concluded that people who are victims of these events during their childhood have consequences in their adult lives, resulting in deficient consequences when building healthy relationships.
Las experiencias adversas en la infancia (EAI) son sucesos desafortunados ocurridos en la niñez del individuo, las cuales pueden llegar a ser traumáticas y afectar al bienestar del sujeto. Por otro lado, las relaciones interpersonales son los lazos creados por la persona con los demás, el mismo que puede verse afectado en caso de sufrir algún tipo de violencia. El objetivo de este estudio es determinar el impacto de las experiencias adversas en las relaciones interpersonales de los adultos jóvenes. Se realizó un estudio con un alcance descriptivo y un enfoque cualitativo. Para esta investigación se utilizó una muestra de 4 participantes adultos jóvenes, dos de Machala de sexo masculino y dos de Pasaje de sexo femenino, donde sus edades rodeaban entre los 20 a 25 años, los cuales sufrieron de algún evento adverso en su infancia. Los instrumentos utilizados son la entrevista semiestructurada, que permitió recolectar información valiosa sobre las experiencias adversas que sufrieron los participantes, y a su vez conocer como estas influyen en las relaciones interpersonales; también se les aplicó el cuestionario de experiencias adversas que evalúa las vivencias negativas que han sufrido en su niñez. Obteniendo como resultado que las EAI influyen en las relaciones interpersonales, se manifestó en la dificultad para confiar en los demás, resolución de conflictos, calidad de establecer nuevas relaciones, descripción personal, actividades cotidianas con eficacia y emociones actuales. Finalmente se concluye que las personas víctimas de estos eventos durante su infancia traen secuelas en su vida adulta, trayendo como consecuencias deficientes al construir relaciones sanas.
Keywords: EXPERIENCIAS ADVERSAS DE LA INFANCIA; RELACIONES INTERPERSONALES; TRAUMA PSICOLÓGICO; VIOLENCIA; ABUSO DE MENORES